2012
DOI: 10.1016/j.ydbio.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

CLASPs function redundantly to regulate astral microtubules in the C. elegans embryo

Abstract: Microtubule dynamics are thought to play an important role in regulating microtubule interactions with cortical force generating motor proteins that position the spindle during asymmetric cell division. CLASPs are microtubule-associated proteins that have a conserved role in regulating microtubule dynamics in diverse cell types. Caenorhabditis elegans has three CLASP homologs in its genome. CLS-2 is known to localize to kinetochores and is needed for chromosome segregation at meiosis and mitosis; however CLS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 49 publications
2
39
1
Order By: Relevance
“…We then quantified the number of astral MTs observed to make contact with the cell cortex. In agreement with the literature (Mimori-Kiyosue et al , 2005; Espiritu et al , 2012), we found that overexpression of CLASP1 resulted in a significant increase in the number of astral MTs contacting the cortex (Figure 5B). In contrast, disruption of the Ran pathway with importazole caused a significant decrease in astral MT/cortex contacts.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We then quantified the number of astral MTs observed to make contact with the cell cortex. In agreement with the literature (Mimori-Kiyosue et al , 2005; Espiritu et al , 2012), we found that overexpression of CLASP1 resulted in a significant increase in the number of astral MTs contacting the cortex (Figure 5B). In contrast, disruption of the Ran pathway with importazole caused a significant decrease in astral MT/cortex contacts.…”
Section: Resultssupporting
confidence: 93%
“…CLASP1 was shown to be important for spindle positioning in multiple organisms, likely due to stabilization of end-on astral MT attachments with the cell cortex (Mimori-Kiyosue et al , 2005; Samora et al , 2011; Espiritu et al , 2012). Our work demonstrates that CLASP1 overexpression can rescue astral MT/cortex contacts in importazole-treated cells without affecting MT elongation speed, showing that RanGTP and CLASP1 affect astral MT dynamics through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These targets included, as expected, proteins involved in centrosome duplication and thus cell division (three centrosomal proteins, SAS-3 SAS-4 and SAS-6, plus-end binding proteins CLS-1 CLASP and EBP-2 EB1 , and TPXL-1 TPX2 ; Table S2; (Espiritu et al, 2012; Kirkham et al, 2003; Leidel et al, 2005; Rogers et al, 2002; Wittmann et al, 2000). The milder effect resulting from depletion of the same proteins later in development suggests that these proteins are largely dispensable for egg-laying apparatus function.…”
Section: Resultsmentioning
confidence: 66%
“…Laser‐severing experiments have additionally shown that the pulling forces in the posterior end of the cell are stronger than those found in the anterior, resulting in spindle displacement from a central location (Grill et al, ; reviewed in Gillies and Cabernard, ). Other studies demonstrated the importance of the CLASP proteins, microtubule‐associated proteins that are necessary for the astral microtubules to reach the cell cortex at the right time during spindle positioning (Espiritu et al, ). Thus, data from the C. elegans embryo overwhelmingly favors a role for pulling forces in generating the asymmetric spindle position during their first division.…”
Section: The C Elegans Embryo: a Model For Polarity‐dependent Spindlmentioning
confidence: 99%